Analisis Perlindungan Hukum Dagang Terhadap Kepentingan Konsumen Dalam Transaksi Dagang Elektronik Dalam Era Digital - Henry Afrillo; Hudi Yusuf (CV. ITTC INDONESIA, 2024)
In the ever-changing digital age, transactions in electronic commerce have become fundamental to global economic activities. Progress in information and communication technology has revolutionized the manner in which individuals purchase, vend, and engage with products and services. Through online platforms, consumers can easily access various products and services from different sellers worldwide. Despite providing unprecedented access and flexibility, electronic commerce transactions also bring new risks that need to be seriously addressed, especially regarding legal protection for consumers. Legal protection in electronic commerce transactions plays a crucial role in ensuring security, fairness, and trust in the electronic trading environment. Consumers engaging in online transactions are often vulnerable to various forms of fraud, misuse of personal data, or contractual inequities. Hence, there is an immediate requirement to establish resilient and efficient legal structures to protect consumer interests in electronic commerce dealings. It is crucial to conduct a thorough examination of current legal frameworks, both domestically and internationally, and to adopt optimal strategies for safeguarding consumers in online transactions to discern the strengths and weaknesses of the current protective measures. Consequently, this study endeavors to investigate the obstacles and remedies concerning the legal safeguarding of consumer interests in electronic commerce transactions during the digital age.